Rumsey family papers
Correspondence among family members; wills; surveys, deeds, plats, and other documents relating to land ownership; personal and business financial records; contracts and other legal documents; sermons; and notes on family history. Correspondence relates to family affairs, health, travel, weather, business, and politics. Places mentioned include Bohemia Manor, Cecil County, Md.; Georgetown, Kent County, Md.; Wilmington, Del.; and Philadelphia, Pa. Included as correspondents or subjects of correspondence are members of the Bayard (Baird), Bordley, Boyer, Brinkle, Everitt (Everett), Pearce, Rigbie (Rigby), and Wright families. Correspondence and accounts (1775-1777) of Philadelphia merchant shipping company, Hodges, Bayard and Company, include subjects such as trade with Europe and arms contracts during the Revolutionary War. Includes a legal document signed by Francis Scott Key and license (1872 May 23) to keep a billiard table issued by Quebec Province.
In part, negative photocopies.
Photocopies produced from originals in the Manuscript Division.
Family of Bohemia Manor, Cecil County, Md. Family members represented include Julia Rumsey Brinkle, Sabina Rumsey Rigbie, Anna Rumsey, Benjamin Rumsey, Charles Rumsey, John Rumsey, John Rumsey, Jr., Margarett Rumsey, Nathan Rumsey, Nathaniel Rumsey, Susan Rumsey, Thomas Rumsey, and William Rumsey.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Key, Francis Scott, -- 1779-1843.; Baird family; Bayard family; Bordley family; Boyer family; Brinkle family; Everett family; Everitt family; Pearce family; Rigby family; Rigbie family; Rumsey family; Wright family; United States. -- Continental Army -- Equipment and supplies; Hodges, Bayard and Company; Licenses -- Québec (Province); Bohemia Manor (Cecil County, Md.); Cecil County (Md.) -- Description and travel; Cecil County (Md.) -- History; Cecil County (Md.) -- Social life and customs; Delaware -- Description and travel; Europe -- Commerce -- Philadelphia (Pa.); Kent County (Md.) -- Description and travel; Maryland -- Description and travel; Maryland -- History -- Colonial period, ca. 1600-1775.; Maryland -- History -- 1775-1865.; Maryland -- Politics and government -- To 1775.; Maryland -- Politics and government -- 1775-1865.; Maryland -- Social life and customs; Pennsylvania -- Description and travel; Philadelphia (Pa.) -- Commerce; Philadelphia (Pa.) -- Commerce -- Europe; Philadelphia (Pa.) -- Description and travel; United States -- History -- Revolution, 1775-1783 -- Equipment and supplies; United States -- Politics and government -- 18th century; Wilmington (Del.) -- Description and travel